Estudio de adaptación de siete Pastos y tres mezclas forrajeras con la utilización de Lactofermento en la Comunidad de San Isidro, parroquia La ,atriz, cantón Pujilí, provincia de Cotopaxi 2018-2019 - Peñafiel Hernández, Juan Diego (2019)
The present investigation was carried out in the San Isidro community, located in the parish of La Matriz, Canton Pujilí, Cotopaxi Province, with the coordinates latitude: 754890, longitude: -9887823 at a height of 2900 meters above sea level, the objective was determined to graze It has the best adaptability to the sector. As treatments, seven different pastures and three forage mixtures are specified, with the application of enriched lactoferment, obtaining twenty treatments, the experimental design implemented was in divided plots (A x B) with three repetitions, where the following variables are analyzed: plant height , cover, microorganisms and soil fungi. Obtaining the following results: The pasture with the best agronomic behavior the T5 treatment (chicory) with 32.92 cm at 43 days, while at 50 days it was the T5 treatment (chicory) with 38.63 cm, although there is no significance in the treatments according to Tukey tests, while the grass with the highest coverage percentage at 57 days for factor A (pastures), was the T15 treatment (Chicory) with 86.33% with this it can be determined that the lactoferment did act in a representative way between treatments and soil fertility. The microbiological analysis of the soil shows that the pastures of the town of San Isidro de Pujilí, the “T15” (Chicory) treatment with 17.32 (CFU / g) obtained the best results in the context of microorganisms present in the soil, while for Fungus count treatments “T12” (red clover), “T15” (Chicory), “T3” (white clover), “T19” (Vicia - oatmeal), “T16” (vicia), “T14” (ryegrass )) with 17.32 (CFU / g) we obtained the best results which are expressed as uncountable for counting colony-forming units per gram (CFU / g) of microorganisms and fungi present in the soil. The results obtained from the biological composition of the lactoferment revealed the existence of molds and yeasts in amounts 3x107 which is expressed as uncountable and of Bacillus sp with 3 (CFU / g), which plays a fundamental role and that helps the decomposition of organic matter and from that get the release of vitamins, minerals, etc .; while the chemical analysis reveals that there are small amounts of macro elements such as N (0.30%), P (0.2%), K (0.90%) and micro elements such as Mg (0.20%), Ca (0.07%), Cu (0.50 ppm) which are indispensable for the soil and therefore for the development of pastures.